4G Voice over LTE สมรภูมิการแข่งขันระหว่างผู้ให้บริการโทรศัพท์เคลื่อนที่ กับผู้ประกอบการ OTT - ไววานิชกิจ นายไพโรจน์ (Journal of Digital Communications, 2017)
Mobile Network Operators around the world currently are under business threats from many Over The Top (OTT) providers who operate their services on the internet. These cause a declining on the voice revenue with a stronger losing marketing portion in the future. Mobile Network Operators are also considering to upgrade their mobile network to optimize the investment and operation cost together with extend the voice service capability towards other wireless access network bearers. The Voice over LTE (VoLTE) technology is the first tactical plan to gain back the market share to the Mobile Network Operators globally.